ETIKA DAN ISU SOSIAL DALAM SISTEM INFORMASI: (TANTANGAN PRIVASI, AKUNTABILITAS, DAN KUALITAS HIDUP DI ERA DIGITAL) - Lailatusolihah; Mohammad Thoriq Al Bariki; Sugeng Listyo Prabowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze ethical and social issues in information systems, focusing on the challenges of privacy, accountability, and quality of life in the digital age. The rapid development of information systems has transformed organizations into integrated digital entities, but has also given rise to various complex ethical issues. This study employs a descriptive qualitative approach using a literature review method, analyzing recent textbooks and international journals. The findings reveal three main conclusions. First, regarding privacy, the use of technologies such as artificial intelligence, cloud computing, and the Internet of Things increases the risk of personal data breaches due to the massive collection and processing of data. Second, regarding accountability, the increasing complexity of digital systems demands transparency and clarity regarding organizational responsibility, particularly in the event of system failures. Third, concerning quality of life, information systems have a dual impact: they enhance efficiency and access to information, yet also create a digital divide and social pressures. In the context of Islamic education management in Indonesia, the implementation of information systems must take into account ethical values such as trustworthiness, justice, and responsibility. Therefore, an integrative approach that combines technological, organizational, and moral aspects is needed to ensure that information systems are not only efficient but also fair and sustainable.